2022
DOI: 10.3390/children9030301
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in Accessibility of Pediatric Formulations: A Cross-Sectional Observational Study of a Teaching Hospital in Northern Thailand

Abstract: The lack of appropriate medicines for children has a significant impact on health care practices in various countries around the world, including Thailand. The unavailability of pediatric medicines in hospital formularies causes issues regarding off-label use and extemporaneous preparation, resulting in safety and quality risks relating to the use of medicines among children. This research aimed to identify missing pediatric formulations based on the experience of healthcare professionals in a teaching hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…From primary health services in Indonesia, pediatric patients aged 0–5 years (74.33%) mostly receive extemporaneous preparations, the majority of which are divided powders (88.36%) and oral suspensions (8.06%) [ 24 ]. In Thailand, 73.5% of pediatric patients receive off-label drugs [ 25 ]. In Brazil, newborns admitted to the neonatal care unit (NCU) also receive compound preparations [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From primary health services in Indonesia, pediatric patients aged 0–5 years (74.33%) mostly receive extemporaneous preparations, the majority of which are divided powders (88.36%) and oral suspensions (8.06%) [ 24 ]. In Thailand, 73.5% of pediatric patients receive off-label drugs [ 25 ]. In Brazil, newborns admitted to the neonatal care unit (NCU) also receive compound preparations [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The risks of drug compounding include formula failure, microbial contamination, calculation errors, patient acceptance issues, health and safety risks, therapeutic risks, clinical consequences, and factors related to clinical risk [ 18 ]. During the drug compounding process, grinding, diluting, adding additional ingredients, etc., errors that affect the efficacy and safety as well as patient acceptance, can occur [ 25 ]. The previous study observed variations in the extemporaneous glucocorticoid for asthma therapy in children.…”
Section: Resultsmentioning
confidence: 99%
“…The tool uses reports of direct observation of attempted/successful administration to confirm and thus expand upon the ages of children and reasons why a medicine may either be classified as AaF or AiF [ 23 , 27 29 ]. The classification ‘Maybe age-appropriate’ indicates that the DF was either authorised but used OL or was an UL medicine.…”
Section: Discussionmentioning
confidence: 99%
“…3 Although commercially available medicines meet the therapeutic needs of most patients, lack of appropriate dosage forms, doses or strengths for certain patient groups is not uncommon. 4 , 5 , 6 , 7 , 8 Notably, extemporaneously compounded medications are more frequently required in the pharmaceutical care of paediatric and geriatric patients. In the case of paediatric patients, licensed formulations may be unavailable.…”
Section: Introductionmentioning
confidence: 99%